2017
DOI: 10.1155/2017/4715861
|View full text |Cite
|
Sign up to set email alerts
|

Controllability Problem of Fractional Neutral Systems: A Survey

Abstract: The following article presents recent results of controllability problem of dynamical systems in infinite-dimensional space. Generally speaking, we describe selected controllability problems of fractional order systems, including approximate controllability of fractional impulsive partial neutral integrodifferential inclusions with infinite delay in Hilbert spaces, controllability of nonlinear neutral fractional impulsive differential inclusions in Banach space, controllability for a class of fractional neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Neutral fractional equations have attracted the interests of many researchers due to the important applications of these equations in physics and engineering, and these equations share some physical characteristics of wave equation due to the physical explanation of these equations as damped waves that have constant propagation velocities [33]. Agarwal et al [34] proved the fractional formulation's existence of neutral differential equations via Caputo fractional derivative.…”
Section: Introductionmentioning
confidence: 99%
“…Neutral fractional equations have attracted the interests of many researchers due to the important applications of these equations in physics and engineering, and these equations share some physical characteristics of wave equation due to the physical explanation of these equations as damped waves that have constant propagation velocities [33]. Agarwal et al [34] proved the fractional formulation's existence of neutral differential equations via Caputo fractional derivative.…”
Section: Introductionmentioning
confidence: 99%
“…Fractional calculus has been of increasing interest to scientists and engineers, arising in mathematical physics, chemistry, modeling mechanical and electrical properties of real phenomena [ 1 , 2 , 3 , 4 , 5 , 6 ]. Fractional calculus has been recognized as a powerful instrument to discover the secret directions of various material and physical processes that deal with derivatives and integrals of arbitrary orders [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…For further introduction to the concept of controllability with diverse applications, refer to major contributions [1][2][3][4][5][6][7][8][9][10] and related references therein. The concept of controllability with applications in engineering has been studied by many authors, a part of which can be found in [11][12][13][14][15][16] and in related references therein. Results obtained in this paper can be used in relevant applied studies in engineering, e.g., [17][18][19][20], for derivation of diverse control regimes.…”
Section: Introductionmentioning
confidence: 99%